Latinx Family Perspectives on Social Needs Screening and Referral during Well-Child Visits. Issue 3 (May 2021) - Spain, Angeline K.; Monahan, Emma K.; Alvarez, Kiara; Finno-Velasquez, Megan
Abstract: Objective: To understand Latinx parent perspectives on screening and referral approaches to identify social determinants of health and address social and material needs during well-child visits and to identify techniques that promote their engagement with these approaches. Study Design: We investigated parent perspectives and engagement with social needs screening and referral practices during well-child visits using focus group methodology. Results: We conducted 17 focus groups ( n = 134 parents and other primary caregivers) with families receiving care at sites operated by eight pediatric primary care clinics. Adding social needs screening and referral shifted the social context of well-child visits for Latinx parents. Participants reported greater engagement with the practices where they perceived an emotional connection with nurses and other clinicians and cultural brokering to ensure their screening responses accurately reflected family needs and priorities. Participants highlighted the importance of having a personal patient–provider relationship as many preferred to discuss social needs outside of the exam room. Clinical Implications: Nurses and other clinicians play a critical role in establishing systems needed to systematically screen and refer families for social needs. Future policy development should consider implications for nursing practice and leadership in adopting these approaches. Abstract : In this study, Latinx parents' perspectives on screening and referral approaches to identify social determinants of health and address social and material needs during well-child visits were evaluated using focus groups. Parents were asked to identify techniques that promote their engagement with screening and referral. They reported greater participation and satisfaction when they perceived an emotional connection with nurses and other clinicians whose efforts to ensure their screening responses accurately reflected family needs and priorities.